2012
DOI: 10.1161/circresaha.111.247213
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Derived From Nuclear Reprogramming

Abstract: The endothelium plays a pivotal role in vascular homeostasis, regulating the tone of the vascular wall, and its interaction with circulating blood elements. Alterations in endothelial functions facilitate the infiltration of inflammatory cells and permit vascular smooth muscle proliferation and platelet aggregation. Therefore, endothelial dysfunction is an early event in disease processes including atherosclerosis, and because of its critical role in vascular health the endothelium is worthy of the intense foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 126 publications
0
41
0
Order By: Relevance
“…17 Therefore, we characterized the endothelial identity of the iEnd cells based on their functional capacity to form capillary lumens when embedded subcutaneously within matrigel plugs in SCID mice. At two weeks post implantation, histological analysis demonstrated that the iEnd cells within plugs maintained expression of human-specific CD31 and could organize to form capillaries (Figure 1G), whereas the parental fibroblasts neither expressed CD31 nor formed tubular structures in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…17 Therefore, we characterized the endothelial identity of the iEnd cells based on their functional capacity to form capillary lumens when embedded subcutaneously within matrigel plugs in SCID mice. At two weeks post implantation, histological analysis demonstrated that the iEnd cells within plugs maintained expression of human-specific CD31 and could organize to form capillaries (Figure 1G), whereas the parental fibroblasts neither expressed CD31 nor formed tubular structures in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…The identification of these FVIII-producing EC subtypes makes it possible to elucidate the genetic determinants that regulate FVIII synthesis. Moreover, LECs can be cultured or generated from induced pluripotent stem cells 47,48 and are accessible for therapeutic manipulation and transplantation 49 : they may serve as an ideal cell source or target for cell-or gene-based FVIII therapy for hemophilia A.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies using these cell sources are now required to determine whether these cell sources provide advantages compared with prior cell types. 127131 …”
Section: Trials Of Cell-based Therapiesmentioning
confidence: 99%